2010
DOI: 10.1111/j.1349-7006.2009.01485.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the prodrugs 5‐fluorocytosine and CPT‐11 on ovarian cancer cells using genetically engineered stem cells: tumor‐tropic potential and inhibition of ovarian cancer cell growth

Abstract: Recent studies have shown that genetically engineered stem cells (GESTECs) to produce suicide enzymes that convert non-toxic prodrugs to toxic metabolites selectively migrate toward tumor sites and reduce tumor growth. In the present study, we evaluated whether these GESTECs were capable of migrating to human ovarian cancer cells and examined the potential therapeutic efficacy of the gene-directed enzyme prodrug therapy against ovarian cancer cells in vitro. The expression of cytosine deaminase (CD) or carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…In turn, SN-38 preferentially kills dividing cancer cells specifically at the tumor sites [30]. We have previously reported that F3.CE cells migrate selectively to tumor sites and they have a therapeutic effect on disseminated neuroblastoma [26, 30], melanoma [28], ovarian cancer [19], breast cancer brain metastasis [17] and medulloblastoma [29] upon administration of prodrug CPT-11. Recently we also have reported that the NSCs expressing the cytosine deaminase (CD).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In turn, SN-38 preferentially kills dividing cancer cells specifically at the tumor sites [30]. We have previously reported that F3.CE cells migrate selectively to tumor sites and they have a therapeutic effect on disseminated neuroblastoma [26, 30], melanoma [28], ovarian cancer [19], breast cancer brain metastasis [17] and medulloblastoma [29] upon administration of prodrug CPT-11. Recently we also have reported that the NSCs expressing the cytosine deaminase (CD).…”
Section: Discussionmentioning
confidence: 99%
“…Previously we have adopted CE/CPT-11 enzyme/prodrug gene therapy approach for treatment of gliomas and disseminated neurobastoma animal models [19, 2630] involving the conversion of a prodrug CPT-11 into SN-38 [30, 34]. CPT-11 (Irinotecan) is known to induce severe toxicities (diarrhea, neutropenia) that limit its clinical use [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HSV-tk system, which relies on the formation of gap junctions between the SC and surrounding target cells for an efficient bystander effect, has shown efficacy in several animal models of cancer, including glioblastoma 55,56 , breast 14 and prostate 57 . Human NSCs harnessing the CE–irinotecan system have proved to be effective in preclinical models of ovarian and lung cancer, as well as medulloblastoma 5860 .…”
Section: Creating Anticancer Stem Cellsmentioning
confidence: 99%
“…[286] For instance, Kim et al engineered immortalized HB1.F3 NSCs to express CE using a retroviral vector to enhance the treatment of ovarian cancer. [283,287] In this study, the authors reported that the engineered NSCs retained their ability to migrate to ovarian tumors and greatly inhibited cancer cell proliferation. Interestingly, the authors compared engineered stem cells using the CD-5-FC system to engineered NSCs expressing CE for the CE-CPT-11 system and found that the CE approach seems to be more promising than the CD approach because the CE approach decreased proliferation with a lower engineered NSC cell number and at a lower concentration of CPT-11 when compared to the concentration of cells and prodrug needed for the CD approach.…”
Section: Engineering Stem Cells For Cancer Therapymentioning
confidence: 86%